(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores Uzbekistan’s journey of economic development under President Shavkat Mirziyoyev’s leadership, focusing on key reform initiatives and strategies. The historical context highlights the country’s transition from a centrally planned to a market-oriented economy. Significant reforms, such as liberalizing the foreign exchange market, simplifying business regulations, and combating corruption, have been pivotal in improving the investment climate. Central to Uzbekistan’s economic strategy is diversifying industries beyond traditional sectors like cotton and mining. Emphasis is placed on promoting manufacturing, agriculture, tourism, and information technology through special economic zones and industrial clusters. Infrastructure development, including transportation and energy, is prioritized to enhance connectivity and regional trade. Uzbekistan actively courts foreign investment through incentives and policy measures, aiming to become a regional economic hub. Trade relations with neighboring countries are strengthened to foster cross-border commerce. Despite challenges, including institutional barriers and bureaucracy, Uzbekistan’s commitment to modernization and growth promises a bright economic future in Central Asia.